Protective effects of Nrf2–ARE activator on dopaminergic neuronal loss in Parkinson disease model mice: Possible involvement of heme oxygenase-1. (25th September 2020) - Inose, Yuri; Izumi, Yasuhiko; Takada-Takatori, Yuki; Akaike, Akinori; Koyama, Yutaka; Kaneko, Shuji; Kume, Toshiaki
Highlights: TPNA10168 protected dopaminergic neurons in a Parkinson disease model. HO-1 protein levels in the brain were upregulated by TPNA10168. HO-1 induced by TPNA10168 was expressed in astrocytes. Abstract: Parkinson disease (PD) is a neurodegenerative disorder characterized by a selective loss of dopaminergic neurons in the substantia nigra, and oxidative stress is thought to contribute to this pathogenesis. The nuclear factor erythroid 2-related factor 2 (Nrf2)–antioxidant response element (ARE) pathway, which induces the production of antioxidant enzymes, is thereby a potential target for therapeutics to reduce neurodegeneration in PD. Previously, we identified TPNA10168 from a chemical library as an activator of the Nrf2–ARE pathway, and the present study examined the effects of TPNA10168 on an in vivo PD model. Subcutaneous administration of TPNA10168 was associated with inhibited dopaminergic neuronal loss and behavioral impairment in 6-hydroxydopamine–induced PD model mice. Heme oxygenase-1 (HO-1) is an antioxidant enzyme expressed downstream of the Nrf2–ARE signaling pathway, and we observed that HO-1 protein levels were upregulated by TPNA10168 in the mouse brain. These results suggest that TPNA10168 inhibits dopaminergic neuronal death in PD model mice, and that upregulation of HO-1 might participate in this effect.